2004
DOI: 10.1902/jop.2004.75.7.933
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Subpopulations in Gingival Overgrowth Induced by Immunosuppressive and Nifedipine Medication

Abstract: Immunosuppressive medication without concomitant nifedipine decreases the numbers of MC(TC) and MC(C) in overgrown gingiva. Chymase-positive mast cells may play a role in formation of gingival overgrowth, especially in patients receiving cyclosporin A (CsA) medication with no concomitant nifedipine. In this respect, nifedipine and CsA are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Similar to gingival overgrowth and oral cancer (Flynn et al 1991;Soory and Suchak 2001;Iamaroon et al 2003;Nurmenniemi et al 2004;Mohtasham et al 2010;Pyziak et al 2013), increased levels of degranulated mast cells and macrophages are associated with neurofibromas. Analysis of initial data suggests that the macrophages in NF1 tissues are not principally synthetic macrophages (Prada et al 2013), but additional studies are required.…”
Section: Gingival Overgrowth and Cancermentioning
confidence: 99%
“…Similar to gingival overgrowth and oral cancer (Flynn et al 1991;Soory and Suchak 2001;Iamaroon et al 2003;Nurmenniemi et al 2004;Mohtasham et al 2010;Pyziak et al 2013), increased levels of degranulated mast cells and macrophages are associated with neurofibromas. Analysis of initial data suggests that the macrophages in NF1 tissues are not principally synthetic macrophages (Prada et al 2013), but additional studies are required.…”
Section: Gingival Overgrowth and Cancermentioning
confidence: 99%
“…Several in vitro studies have pointed out the potential role of mast cells inducing gingival fibroblast proliferation and collagen synthesis [65]. A recently published study demonstrated that mast cell tryptase and chymase enzymes were expressed significantly higher in DIGO tissues compared to healthy gingiva and may contribute to alterations in basement membranes [66]. In addition, tryptase can interact with a number of cell types and has been shown to be mitogenic for fibroblasts [67] and epithelial cells [68].…”
Section: Mast Cell Proteasesmentioning
confidence: 99%
“…It is now thought that mast cell-specific proteases (chymase and tryptase) represent the main criterion of differentiation: mast cells containing only tryptase (MC T ) can be distinguished from those containing both tryptase and chymase (MC TC ). Importantly, in several models both MC T and MC TC were present and directly involved in gingival fibrosis [8, 12]. Chronic periodontitis and fibrosis involve a common sequence of events requiring the interaction of endothelial cells with infiltrating mast cell.…”
Section: Gingival Mast Cells and Fibrosismentioning
confidence: 99%
“…Mast cells synthesize renin and release during degranulation that can generate Ang II from Ang I [21, 30]. Nurmenniemi et al 2004 have demonstrated the augmented mast cell and its enzyme chymase and tryptase in healthy human gingival connective tissue [8]. Despite the great number of studies on mast cell populations, at the present time studies regarding the stimulation of local RAS by mast cells in human gingiva are very few.…”
Section: Renin Angiotensin System and Mast Cellmentioning
confidence: 99%
See 1 more Smart Citation